Impact of climate change on agricultural production and food security: a review on coastal regions of Bangladesh - MS Hossain (International Journal of Agricultural Research, Innovation and Technology, 2018)
Bangladesh is severely vulnerable to climate change and its devastation on coastal livelihood and food security has been substantiated. Climate induced hazards will lead to food insecurity directly and indirectly by affecting the coastal biophysical and socioeconomic states. This review article found the potential impacts on coastal agricultural, livestock and fisheries sectors those are the main source of livelihood and food security to coastal people. Furthermore, most of the rural coastal people are hard poor in which women are major in portion and contribute to ensure food security for the entire family. Scrutinizing on ‘vulnerability’ revealed that it is not gender neutral and socio-economically underprivileged groups and marginal people are invaded disproportionately in which women is ranking in the top of the order. Hence, existing gender-poverty nexus along with socio-economic and political aspects make women more endangered to climate vulnerability and food security. It also found that existing policies and adaptation mechanisms failed to address the influence of powers on marginalize women and growing trend of feminization of food insecurity. In addition, also found the necessity for immediate pertinent caucus before the onset of this imminent concernment by aggregating gender and identified vulnerable groups.